Statins use amidst the pandemic: prescribing, dispensing, adherence, persistence, and correlation with COVID-19 statistics in nationwide real-world data from Poland - Kardas, Przemysław; Kwiatek, Angelika; Włodarczyk, Piotr; Urbański, Filip; Ciabiada-Bryła, Beata (Frontiers in Pharmacology, 2024)
Background Adherence to medications presents a significant challenge in healthcare. Statins, used in primary and secondary prevention of cardiovascular disease, are of particular importance for public health. The outbreak of the COVID-19 pandemic resulted in additional healthcare system-related barriers impeding the execution of therapies. This study aimed to assess the use of as well as adherence and persistence to statins in a national cohort of 38 million of Polish citizens during pandemic. Methods A retrospective analysis of prescription and dispensation data for all statins users from the national payer organization covering the years 2020–2022 was conducted. Medication adherence was assessed using the Medication Possession Ratio, for persistence the 30-day cut-off was accepted. National data on COVID-19 cases and COVID-19 related deaths were obtained from ECDC. Results The analysis identified 7,189,716 Polish citizens (approximately 19% of Polish population) who were dispensed at least 1 pack of statins within the study period. Over that time, there was a continuous significant increasing trend in prescribing and dispensing of statins. Despite a total increase of 18.9% in the number of prescribed tablets, the percentage of tablets dispensed remained similar, averaging 86%. Overall percentage of adherent patients was 48.2%. For a random sample of 100,000 patients, the mean period of continuous therapy in 2022 was 6.2+/- 5.3 months. During the lockdown period, the mean number of prescribed and dispensed tablets was lower by 6.8% and 5.9%, respectively (p < 0.05). However, fluctuations in the number of COVID-19 cases or COVID-19-related deaths per week had no major impact on the prescribing and dispensing of statins. Conclusion Over the time of pandemic, there was a continuous increase in the number of statin tablets prescribed and dispensed in Poland. This suggests that, despite the potential limitations posed by COVID-19, access to statins remained easy, which may be attributed to the mass-scale implementation of the national e-prescription system. However, it is crucial to realise that approximately 1/7 of prescribed statin doses were never dispensed, and the overall levels of adherence and persistence were low. This underscores the necessity for concerted efforts to change this scenario in Poland.